The origin and depositional processes of shell layers in the Jurassic Ziliujing Formation in the Sichuan Basin and their influences on petroleum accumulation - Bao, Hanyong; Shu, Yi; Wang, Qiming; Zheng, Youheng; Chen, Miankun; Lu, Yongchao; Liu, Haotian; Peng, Wei (Frontiers in Earth Science, 2025)
Unlike other lacustrine shale formations in which carbonate and siliceous interlayers are intercalated, the Dongyuemiao shale is different due to its abundant shell laminae and interlayers. Due to the lack of studies on shell laminae and interlayers, their influence on oil accumulation is still unclear. This study integrated total organic carbonand X-ray diffractiondata, core and thin section observations, field-emission scanning electron microscopy, major and trace element data, and helium porosimetry to investigate the depositional environment and porosity structure of shell interlayers in the shale in the first member of the Dongyuemiao shale (Dong-1 member) and their impact on petroleum accumulation. Results show that Dong-1 member was deposited in a sub-lacustrine fan, and shells and shell fragments were transported by gravity flow. Shells and shell fragments were transported and broken up to under different hydrodynamic conditions, and formed laminae, interlayers, and thick interlayers of shell fragments. In the shell laminae (≤1 cm) and thin interlayers (1-10 cm), micro-scale dissolution pores and microfractures formed in the shell clasts can effectively connect the dissolution pores and black shale matrix. The thick shell interlayers (≥10 cm) lack porosity networks and prevent petroleum migration. The shell laminae and thin interlayers are the storage space and pathway for petroleum storage and migration, while the thick shell layers are seals that prevent petroleum leakage. This integrated study of a shell-rich shale can provide a reference for petroleum exploration and quantitative evaluation of the resources.